The Rise of Tunnel Endoscopic Surgery: A Case Report and Literature Review - Mingyan Cai; Jinzhong Chen; Pinghong Zhou; Liqing Yao (Case Reports in Gastrointestinal Medicine)
There has been booming interest in natural orifice transluminal surgery since it was first described. Several techniques first developed for the safe transluminal access now derive into independent endoscopic surgical procedures. In this paper, we describe a case treated by a novel procedure by submucosal tunnelling technique and provide a literature review of the rise of tunnel endoscopic surgery.